Mechanism of interactions between tripeptide NCW on cellular membrane using molecular dynamic simulation - Wu, Sijia; Zhuang, Hong; Yan, Haiyang; Mao, Chen; Wang, Bing; Zhou, Guangdong; Tian, Ge (Frontiers in Nutrition, 2022)
Tripeptide NCW identified in Mizuhopecten yessoensis has been shown to possess in vivo antihypertensive effect. However, the poor understanding of the absorption of NCW across the membrane limits its application. In this study, we have investigated the interaction of NCW with DPPC membrane via 400 ns all-atom molecular dynamic simulation using GROMACS software. The structural variations of NCW during absorption, the location and distribution of NCW in the membrane, and the effect of NCW on the properties of membranes during simulation were analyzed to understand the dynamic behavior of NCW in DPPC membrane system. The results suggested that the structures of NCW were stable during simulation. Further, NCW could bind on the surface of the DPPC membrane and enter the hydrophobic interior of the DPPC membrane. Residue Try played an important role in the absorption of NCW across the membrane. Hydrogen bonds and hydrophobic interactions stabilized the interaction of NCW with the membrane. All the above studies analyzed the interaction mechanism between NCW and DPPC membranes at the atomic level and laid the foundation for further transmembrane studies of NCW.